2020
DOI: 10.1093/rap/rkaa067
|View full text |Cite
|
Sign up to set email alerts
|

Increased number of cases of giant cell arteritis and higher rates of ophthalmic involvement during the era of COVID-19

Abstract: Objectives Our centre offers a fast-track assessment service for patients with suspected giant cell arteritis (GCA) and this service continued to operate during the Covid-19 pandemic. During and immediately following the peak of the Covid-19 pandemic in the UK we observed an increase the number of patients diagnosed with GCA plus an increased number of patients with visual complications. Our aim was to investigate this further. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Luther et al stated that while 28 patients were diagnosed with GCA in 2019, between April 2020 and June 2020, the number of new GCA cases was 24, suggesting that viral etiopathogenesis of GCA might exist. Higher rates of ocular manifestations of GCA were also observed during the pandemic; however, none of the patients diagnosed with GCA had any symptoms suggesting COVID-19 [ 5 ]. Mulhearn et al observed the excess of 33 cases of GCA in 2020 in comparison with 2019, which they reported might have been caused by the damage to the endothelium and activation of T-helper cell type 1 cellular immunity and the monocyte-macrophage system [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Luther et al stated that while 28 patients were diagnosed with GCA in 2019, between April 2020 and June 2020, the number of new GCA cases was 24, suggesting that viral etiopathogenesis of GCA might exist. Higher rates of ocular manifestations of GCA were also observed during the pandemic; however, none of the patients diagnosed with GCA had any symptoms suggesting COVID-19 [ 5 ]. Mulhearn et al observed the excess of 33 cases of GCA in 2020 in comparison with 2019, which they reported might have been caused by the damage to the endothelium and activation of T-helper cell type 1 cellular immunity and the monocyte-macrophage system [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our experience with GCA is in fact quite the opposite to that reported by Luther et al, who recently identified an increase of GCA cases as well as of cases with visual impairment during the COVID-19 pandemic. 3 In conclusion, our experience shows that patients with systemic vasculitis sought help and did not suffer from significant delays in receiving healthcare even during the pandemic.…”
mentioning
confidence: 69%
“… 14 Interestingly, presentation with otalgia and visual loss were reported with normal ESR in cases that showed positive COVID-19. 15 Literature from several parts of the world observed the association of COVID-19 and giant-cell arteritis. 16 - 18 …”
Section: Discussionmentioning
confidence: 99%
“…14 Interestingly, presentation with otalgia and visual loss were reported with normal ESR in cases that showed positive COVID-19. 15 Literature from several parts of the world observed the association of COVID-19 and giant-cell arteritis. [16][17][18] Therefore, it is wise to suspect GCA in those over 50 years of age presenting with symptoms in one or both eyes, or persistent frontal or parietal headache (Table 1).…”
Section: Discussionmentioning
confidence: 99%